Visceral Organ Weight of Pengging Duck after the Addition of Nanochitosan as Feed Additive - Khevalin Kwardoyo; Sunarno Sunarno; Siti Muflichatun Mardiati (Biosaintifika: Journal of Biology & Biology Education, 2023)
The productivity of pengging ducks is determined by optimizing the function of the body's organs. The feed consumed greatly determines the growth and development of the internal organs in the pengging duck. Nanochitosan is a polysaccharide that has potential as a feed additive which functions to increase feed digestibility, nutrient absorption, promote growth to help optimize the function of visceral organs. This study aims to analyze the effect of nanochitosan as a feed additive on the function of the visceral organs of pengging ducks in terms of the weight of the visceral organs. The visceral organs studied included the ventriculus, intestines, liver, pancreas, spleen, and heart. This study was designed in a completely randomized design (CRD) consisting of 5 treatments (0; 2.5; 5; 7.5; 10 g nanochitosan/kg feed) with 5 replications. Nanochitosan feed additive treatment was given for 8 week. Variables that were measured in this study included weight of ventriculus, intestinal, liver, pancreas, spleen, and heart of pengging ducks. The research data showed that nanochitosan as a feed additive had no significant effect on visceral weight of pengging ducks (P0.05). The conclusion of this study is that nanochitosan as a feed additive does not cause changes in the function of the visceral organs based on the indication of the weight of the visceral organs measured, namely the ventricles, intestines, liver, pancreas, spleen, and heart. The novelty of this research is the use of nanochitosan as a feed additive to improve the performance of penging ducks by maintaining the size of the visceral organs. It is hoped that the results of this research on nanochitosan feed additive can be used by local laying duck farms in Indonesia because it is safe and as an effort to improve the performance and productivity of ducks.